Occurrence characteristics and influencing factors of movable fluid in the medium- and low-permeability reservoirs of the Es32+3 submember of the Gao3102 fault block in the Gaoshangpu Oilfield - Ruxian Chen; Jiagen Hou (地质科技通报, 2023)
Objective In order to clarify the occurrence characteristics of movable fluids in medium- and low-permeability reservoirs, so as to better guide the increase in oil reserves and production in the oilfield. Methods This study focuses on the medium- and low-permeability sandstone reservoirs in the Es32+3 submember of the Gao3102 fault block in the Gaoshangpu Oilfield. Based on thin section data, whole-rock diffraction analysis, high-pressure mercury injection curves, closed core nuclear magnetic resonance data, scanning electron microscopy, and oil-water phase permeability curves, the occurrence characteristics and influencing factors of movable fluids in reservoirs with different pore structures were conducted. Results The results show that (1) the movable fluid saturation of reservoirs with different pore structures varies greatly. The T2 spectrum of the nuclear magnetic resonance of the class Ⅰ medium porosity and medium throat reservoir is bimodal with left low and right thigh, and the average saturation of movable fluid is 61.14%. The T2 spectrum of the nuclear magnetic resonance of the class Ⅱ medium and small pore fine throat reservoir shows a double peak type with left high and right high, and the average of movable fluid saturation is 45.24%. The T2 spectrum of the nuclear magnetic resonance of the class Ⅲ fine porous micro throat reservoir shows a double peak type of left high and right low, and the average of movable fluid saturation is 30.45%. The T2 spectrum of the nuclear magnetic resonance of the class Ⅳ microporous micro throat reservoir shows a left high single peak, and the average saturation of movable fluid is 13.86%. (2) The macroscopic physical properties, microscopic pore structure, clay mineral content and reservoir wettability of the reservoir jointly control the occurrence characteristics of the movable fluid. Among them, the microscopic pore structure is a key factor in the occurrence of movable fluid. The larger the pore throat radius is, the better the reservoir seepage capacity, the lower the clay mineral content is, the weaker the reservoir wettability is, and the higher the movable fluid saturation is. Conclusion The results of this research can provide a reasonable scientific basis for high-efficiency water injection development of the Es32+3 reservoir in the Gaoshangpu Oilfield.